Barriers and facilitators influencing facility-based childbirth in rural Haiti: a mixed method study with a convergent design. Issue 8 (23rd August 2020) - Raymondville, Maxi; Rodriguez, Carly A; Richterman, Aaron; Jerome, Gregory; Katz, Arlene; Gilbert, Hannah; Anderson, Gregory; Joseph, Jean Paul; Franke, Molly F; Ivers, Louise C
Abstract : Introduction: Haiti has the highest maternal mortality rate in the Western Hemisphere. Facility-based childbirth is promoted as the standard of care for reducing maternal and neonatal mortality. We conducted a convergent, mixed methods study to assess barriers and facilitators to facility-based childbirth at Hôpital Universitaire de Mirebalais (HUM) in Mirebalais, Haiti. Methods: We conducted secondary analyses of a prospective cohort of pregnant women seeking antenatal care at HUM and quantitatively assessed predictors of not having a facility-based childbirth at HUM. We prospectively enrolled 30 pregnant women and interviewed them about their experiences delivering at home or at HUM. Results: Of 1105 pregnant women seeking antenatal care at the hospital between May and December 2017, 773 (70%) returned to the hospital for facility-based childbirth. In multivariable analyses, living farther from the hospital (adjusted OR (AOR)=0.73; 95% CI 0.56 to 0.96), poverty (AOR=0.93; 95% CI 0.88 to 0.99) and household hunger (AOR=0.45; 95% CI 0.26 to 0.79) were associated with not having a facility-based childbirth. Primigravid women were more likely to have a facility-based childbirth (AOR=1.34, 95% CI 1.02 to 1.76). Qualitative data provided insight into the value women place on traditional birth attendants ('matrons') during home-based childbirths. While women perceived facility-based childbirths as better equipped to handle birth complications, barriers such as distance, costs of transportation and supplies, discomfort of facility birthing practices and mistreatment by medical staff resulted in negative perceptions of facility-based childbirths. Conclusion: Pregnant women in rural Haiti must overcome substantial structural barriers and forfeit valued support from traditional birth attendants when they pursue facility-based childbirths. If traditional birth attendants could be involved in care alongside midwives at facilities, women may be more inclined to deliver there. While complex structural barriers remain, the inclusion of matrons at facilities may increase uptake of facility-based childbirths, and ultimately improve maternal and neonatal outcomes.